High rate treatment of hospital wastewater using activated sludge process induced by high-frequency ultrasound - Karami, Nasim; Mohammadi, Parviz; Zinatizadeh, Aliakbar; Falahi, Farzaneh; Aghamohammadi, Nasrin (Elsevier, 2018)
The biomass concentration of conventional activated sludge (CAS) process due to low sludge sedimentation in clarifiers is limited to 3000 mg/L. In this study, high-frequency ultrasound wave (1.8 MHz) was applied to enhance the CAS process performance using high Mixed Liquor Suspended Solid (MLSS) concentration. The study conducted using a pilot scale CAS bioreactor (with and without ultrasound) and their performance for treating a hospital wastewater were compared. Experimental conditions were designed based on a Central Composite Design (CCD). The sets of data analyzed, modeled and optimized using Response Surface Methodology (RSM). The effect of MLSS concentration 3000–8000 mg/L and hydraulic retention time (HRT) 2–8 h are considered as operating variables to investigate on process responses. The obtained results showed that high-frequency ultrasound was significantly decreased the sludge volume index (SVI) 50% and effluent turbidity about 88.5% at high MLSS. Also, observed that COD removal of both systems was nearly similar, as the maximum COD removal for sonicated and non-sonicated systems were 92 and 92.5% respectively. However, this study demonstrates that the ultrasound irradiation has not had any negative effect on the microbial activity.